Territory spatial planning and national governance system in China. (March 2021) - Liu, Yansui; Zhou, Yang
Highlights: Problems faced by China's spatial planning were investigated. Territorial spatial planning system and its role in China's national spatial governance were explained. Territorial spatial planning helps to improve national space governance capabilities. Territorial spatial planning legislation will be a milestone in space governance. Countermeasures to promote the implementation of China's territorial space planning have been put forward. Abstract: Spatial planning refers to the long-term planning and overall arrangement of land resources and space layout under the jurisdiction of a country or region government, aiming to achieve effective control and scientific management of territorial space and promote the balance between development and protection. It is generally considered as an effective instrument for promoting space governance and regional sustainable development. This study systematically reviewed the evolution history of China's spatial planning and the key issues it faces or brings, then analyzed the major measures and potential challenges taken by the country, and finally put forward countermeasures and suggestions to promote the establishment and implementation of national territory spatial planning (NTSP). Results demonstrated that as the largest developing country in the world, due to the lack of unified spatial planning system and superior laws, there are many problems in China's spatial planning, such as various types, overlapping conflicts, complex approval process and frequent revision of planning, and difficulties in planning implementation, which has led to the imbalance of territory spatial development, deterioration of ecological environment, tightening of resource constraints and regional unbalance development. To solve these problems, China is innovating to take its territory spatial as a system to establish a unified NTSP system, and promoting the transformation of spatial planning from multisector industry or special planning to integrated NTSP. At the same time, China is actively promoting the NTSP legislation, which will have a milestone role in promoting state affairs and space governance by law. However, the NTSP system's establishment still faces many challenges, and the its formulation and implementation need to consider the background of the times, follow the law of modernization development, and adapt to local conditions in combination with national conditions.